Factors influencing place of death and disenrollment among patients receiving specialist palliative care - Di Nitto, Marco; Artico, Marco; Piredda, Michela; De Maria, Maddalena; Magnani, Caterina; Marchetti, Anna; Mastroianni, Chiara; Latina, Roberto; De Marinis, Maria Grazia; D'Angelo, Daniela (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: Place of death and disenrollment from specialized palliative care services (SPCSs) are two aspects that determine service utilization. These aspects should be determined by patient needs and preferences, but they are often associated to patient sociodemographic or contextual characteristics. The aim of this study was to describe which factors are associated with utilizing SPCSs in terms of place of death and disenrollment.Methods: Retrospective cohort study. Patients (>18 years) who died or were disenrolled during SPCSs utilization. Two hierarchical regression models were performed, and variables were categorized in predisposing, enabling, and need factors according to the Andersen behavioral model of health services use.Results: We included 35,869 patients (52,5% male, mean age 74,6 ± 12,3 SD), where 17,225 patients died in hospice and 16,953 at home, while 1,691 patients were disenrolled. Dying at home was associated with older age, oncological diagnosis, painful symptoms and longer survival time. Instead, service disenrollment was associated with less education, longer wait time and longer length of stay.Conclusions: SPCS utilization was not influenced only by patient need, but also by other factors, such as social and contextual factors. These factors need to be considered by health care providers and efforts are needed for 1) identifying barriers and implementing effective interventions to support patients and caregivers in their preferred place of care and death and 2) for avoiding SPCS disenrollment with an increased probability of aggressive treatments and worse quality of life for patients.